Citizens' Satisfaction with Power-sharing in Zanzibar: A Comprehensive Study - Haji, Moh'd Juma; Kessy, Ambrose Theobald (Universitas Brawijaya, 2024)
Zanzibar, A semi-autonomous nation of Tanzania has had a turbulent political conflict that resulted in a significant loss of life, injuries, and civic unrest. The birth of contestation of the conflict is the electoral process associated with political identity on the Island. 2010, Zanzibar adopted a power-sharing system through a referendum and subsequent constitutional amendment. The aim was to make power-sharing representable to the citizens and deeply rooted in society. Over a decade has passed, and it employs a mixed-method approach that combines quantitative and qualitative methods. Two hundred eighty-seven (287) respondents participated in the survey, and 28 individuals engaged in interviews. The findings indicate that the citizens are satisfied with some aspects of power-sharing. They are satisfied with power-sharing in promoting unity and neutralizing identity politics. Evidence of this is reflected in citizens' cooperation and equitable treatment among different ethnicities and affiliations. However, a critical concern emerges in peace-building, particularly in managing electoral violence. The citizens argued that the electoral institutions are not well managed. This emphasizes having an impartial electoral system that is fair, transparent, and honest to make citizens trust the electoral process in Zanzibar.